FRI0520 THE HUMAN ENTHESIS CONTAINS POPULATIONS OF MESENCHYMAL STEM CELLS WITH DISTINCT FUNCTIONAL CHARACTERISTICS. (June 2019) - Russell, Tobias; Watad, Abdulla; Bridgewood, Charlie; Khan, Almas; Millner, Peter; Loughenbury, Peter; Rao, Abhay S.; Dunsmuir, Robert; Baboolal, Thomas; Jones, Elena; Mcgonagle, Dennis; Cuthbert, Richard
Abstract : Background: Ankylosing spondylitis (AS) is associated with entheseal inflammation and new bone formation. Resident populations of lymphocytes have been identified at the enthesis that on stimulation with IL-23 produce pro-inflammatory cytokines including IL-17A and IL-22 (1) which drive inflammation and may also influence osteogenesis. Surprisingly, enthesis resident mesenchymal stem cells (MSCs) have not been phenotypically or functionally characterised. Objectives: To determine if human enthesis including entheseal soft tissue and peri-entheseal bone harbours a population of MSCs. Furthermore, to investigate the effect of spondyloarthritis associated pro-inflammatory cytokines on MSC osteogenesis. Methods: Samples from healthy the spinous process and interspinous ligament (male = 5, female = 10, median age = 19) were divided into entheseal soft tissue (EST) and peri-entheseal bone (PEB) and enzymatically digested (1). MSCs content was assessed using a CFU-F assay. Flow cytometry was used to examine expression of MSCs specific markers in plastic adherent cultures. Following osteogenic, chondrogenic and adipogenic inductions, osteogenesis was qualitatively by alkaline phosphatase and alizarin red staining and quantitatively by measurement of calcium accumulation. Chondrogenesis and adipogenesis were assessed using glycosaminoglycan assay and oil red o staining respectively. Osteogenic cultures were also supplemented with IL-17A (50ng/ml), IL-22 (10ng/ml) or TNF-α (1ng/ml). Results: As a proportion of total cellularity EST developed approximately 5 fold more colonies than matched PEB (p<0.0001). Cultured cells were overwhelmingly positive for expression of MSC markers CD73, CD90, CD105 (PEB median 98.66% range: 95.17-98.96%, EST median 98.42% range: 87.69-98.7%) and negative for CD14, CD19, CD45 and HLA-DR (PEB median 0.34% range: 0-2.91%, EST median 1.1% range: 0-2.53%) however some CD34 expression was noted particularly in EST cultures (median 3.74% range: 0-29%). Both populations were capable of tri-lineage differentiation, although PEB MSCs had greater osteogenic (p<0.025) and lower adipogenic (p<0.05) potential than matched EST MSCs. Addition of IL-22 (p<0.01) or IL-17A (p<0.005) caused a significant decrease in the calcium deposited in PEB MSCs but not in EST MSCs. Conclusion: Both the EST and PEB contain cells that meet the ISCT criteria defining MSCs. However, MSCs from these sources are functionally distinct in terms of their differentiation potential and response to inflammatory cytokines. The cytokines tested had a negative influence on osteogenesis in the conditions tested. References: [1] CUTHBERT, R.J., E.M. FRAGKAKIS, R. DUNSMUIR, Z. LI, M. COLES, H. MARZO-ORTEGA, P.V. GIANNOUDIS, E. JONES, Y.M. EL-SHERBINY and D. MCGONAGLE. Brief Report: Group 3 Innate Lymphoid Cells in Human Enthesis. Arthritis Rheumatol, 2017, 69(9), pp.1816-1822. Disclosure of Interests: Tobias Russell Grant/research support from: PhD Project is funded by Novartis., Abdulla Watad: None declared, Charlie Bridgewood: None declared, Almas Khan: None declared, Peter Millner: None declared, Peter Loughenbury: None declared, Abhay S Rao: None declared, Robert Dunsmuir: None declared, Thomas Baboolal: None declared, Elena Jones: None declared, Dennis McGonagle Consultant for: Lilly, Novartis UCB, Speakers bureau: Lilly, Novartis UCB, Richard Cuthbert: None declared